Mitigation Of Global Challenges And Their Potential Impact On Indonesian Migrant Workers - Mahdi, Uteng; Rano MA Tilaar; Kriara Latifah Dinar; Sharleen Aulia Redian; Daffa Nauvaldy; Dhandy Wibisono (SEAN Institute, 2024)
Indonesian migrant workers (TKI) are an important element in the national economy, both through the remittances they send and their contribution in strengthening bilateral relations with destination countries. However, TKI also face various increasingly complex global challenges, including uncertainty in immigration policies, the impact of climate change, and technological transformation and digitalization. This paper aims to examine these challenges in depth, analyze their potential impacts, and formulate mitigation strategies that focus on empowering TKI and the Indonesian diaspora. With a comprehensive approach based on legal protection, skills improvement, and diaspora mobilization, it is hoped that the welfare of TKI can be maintained and their competitiveness can increase amidst global dynamics.